Przygotowanie pacjentów z cukrzycą typu 2 do profilaktyki zespołu stopy cukrzycowej = Preparing patients with type 2 diabetes to prophylaxis of diabetic foot - Beata Kropornicka; Bożena Baczewska; Aleksandra Dadej; Ewa Krzyżanowska; Robert Łuczyk; Cecylia Olszak; Elżbieta Nowicka; Regina Lorencowicz; Bożena Muraczyńska (Kazimierz Wielki University, 2017)
Kropornicka Beata, Baczewska Bożena, Dadej Aleksandra, Krzyżanowska Ewa, Łuczyk Robert, Olszak Cecylia, Nowicka Elżbieta, Lorencowicz Regina, Muraczyńska Bożena. Przygotowanie pacjentów z cukrzycą typu 2 do profilaktyki zespołu stopy cukrzycowej = Preparing patients with type 2 diabetes to prophylaxis of diabetic foot. Journal of Education, Health and Sport. 2016;6(11):311-324. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167141 http://ojs.ukw.edu.pl/index.php/johs/article/view/3999   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 17.11.2016.       Przygotowanie pacjentów z cukrzycą typu 2 do profilaktyki zespołu stopy cukrzycowej Preparing patients with type 2 diabetes to prophylaxis of diabetic foot   Beata Kropornicka1, Bożena Baczewska1, Aleksandra Dadej1, Ewa Krzyżanowska1, Robert Łuczyk1, Cecylia Olszak1, Elżbieta Nowicka1, Regina Lorencowicz2, Bożena Muraczyńska3   1 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2 Katedra i Zakład Pielęgniarstwa Neurologicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w  Lublinie 3 Katedra Chirurgii i Pielęgniarstwa Chirurgicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie   Streszczenie Wstęp. Edukacja chorych na cukrzycę wpływa na obniżenie ryzyka późnych powikłań cukrzycy. Celem pracy było określenie poziomu wiedzy pacjentów z cukrzycą typu 2 w zakresie profilaktyki zespołu stopy cukrzycowej. Materiał i metoda. Metodą wykorzystaną w pracy był sondaż diagnostyczny, techniką testowanie wiedzy pacjentów, a narzędziem autorski test wiadomości. Badania zostały przeprowadzone wśród 100 dorosłych pacjentów z cukrzycą typu 2 w SPSK4 w Lublinie w 2014 roku. Wyniki badań. Pacjenci z cukrzycą posiadali dużą wiedzę w zakresie zalecanej diety, wysiłku fizycznego i zasad monitorowania cukrzycy. Deficyt dotyczył znajomości istoty i czynników ryzyka zespołu stopy cukrzycowej. Poziom wiedzy badanych był związany z ich wykształceniem, czasem trwania choroby i miejscem zamieszkania. Chorzy z wykształceniem wyższym i średnim posiadali wyższy poziom wiedzy niż pacjenci z wykształceniem zawodowym i podstawowym. Dłuższy czas trwania choroby wiązał się z wyższym poziomem wiedzy respondentów. Osoby mieszkające na wsi miały większy deficyt wiedzy niż badani zamieszkali w mieście. Płeć i wiek badanych nie wpływały na ich przygotowanie do profilaktyki zespołu stopy cukrzycowej. Wnioski. Przygotowanie chorych do profilaktyki zespołu stopy cukrzycowej było niewystarczające. Badania wskazują na konieczność zintensyfikowania działań edukacyjnych środowiska medycznego wśród chorych z cukrzycą.   Słowa kluczowe: profilaktyka, stopa cukrzycowa, edukacja chorych   Abstract Backgroud. Education of diabetic patients reduces the risk of long-term diabetic complications.  The purpose of study was to assess the knowledge of patients with type 2 diabetes on the prophylaxis of diabetic foot. Material and methods. The problem was investigated by means of a survey to test patients' knowledge (technique) using test of knowledge as a tool. The survey was carried out among 100 patients with type 2 diabetes in PSK4, Lublin, in 2014. Results. The diabetic patients demonstrated wide knowledge on the recommended diet, physical effort and rules of monitoring diabetes. However certain deficit was found in the area of knowledge on risk factors for diabetic foot and the problem itself. The level of knowledge correlated with respondents' education,  disease duration and the place of living. The patients with higher and secondary education presented higher level of knowledge compared with the patients with vocational and primary education. Longer period of disease duration correlated with better knowledge on the disease. The respondents living in the country showed higher deficit compared to the respondents from the city. The age or gender of the respondents did not affect their preparation to the prophylaxis of diabetic foot. Conclusions. The results found the patients were not sufficiently prepared to the prophylaxis of diabetic foot. The results suggest the need to intensify educational activities of medical personnel addressed at diabetic patients.   Keywords: prevention, diabetic foot, patient education